A review of global trends in CITES live wildlife confiscations - D'Cruze, N; Macdonald, D (Pensoft Publishers, 2016)
We assessed the global scope and scale of confiscated live wild vertebrates using information from the annual Convention on International Trade in Endangered Species of Flora and Fauna (CITES) reports. These reports documented a total of 64,143 individual animals (from 359 species), confiscated by 54 countries party to CITES, between 2010 and 2014. Reptiles represented 95% of individuals seized and posed a particular management challenge during this time. From a conservation perspective, 19% of all individuals reported as seized are currently considered as “Threatened” according to the IUCN Red List and 1% are listed on CITES Appendix I. During this time period, relevant national enforcement agencies have had to effectively detect and quickly deal with illegal live shipments involving a diverse array of vertebrate species with varying psychological attributes, physiological attributes and conservation value. However, we raise pre-existing concerns that CITES records are incomplete, with no data on live seizures provided by 70% of countries party to CITES. Data on the disposal of confiscated live animals is also lacking as providing them is not currently a formal CITES requirement. This lack of information impedes the proper allocation of available resources and prevents the effective monitoring and evaluation of management outcomes. Therefore, we recommend that the management authorities improve reporting compliance, and we encourage the CITES trade database (and other associate national, regional and global databases) to include information on the disposal of all live seizures.